Свидание с Нефертити - Тендряков Владимир Федорович (1988)
Экземпляры: Селтинская районная библиотека (к/х) (20220901) / Инвентарный номер: 134023 / Цена: / Авт.знак: Т 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6